2008
DOI: 10.1093/pasj/60.3.653
|View full text |Cite
|
Sign up to set email alerts
|

On Black Hole Mass Estimation from X-Ray Spectra of Ultraluminous X-Ray Sources

Abstract: We propose a methodology to derive a black-hole mass for super-critical accretion flow. Here, we use the extended disk blackbody (extended DBB) model, a fitting model in which the effective temperature profile obeys the relation $T_{\rm eff} \propto r^{-p}$, with $r$ being the disk radius and $p$ being treated as a fitting parameter. We first numerically calculate the theoretical flow structure and its spectra for a given black-hole mass, $M$, and accretion rate, $\dot{M}$. Through fitting to the theoretical s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 55 publications
2
49
0
Order By: Relevance
“…(confirmed also by the numerical results of Vierdayanti et al 2008), but such a BH would be far below Eddington at the observed luminosity »Ĺ 2 10 39 erg s −1 , contrary to our initial slim disk assumption. Therefore, the slim disk model cannot be self-consistently applied to the spectrum of ULX-1.…”
Section: () ()supporting
confidence: 76%
See 2 more Smart Citations
“…(confirmed also by the numerical results of Vierdayanti et al 2008), but such a BH would be far below Eddington at the observed luminosity »Ĺ 2 10 39 erg s −1 , contrary to our initial slim disk assumption. Therefore, the slim disk model cannot be self-consistently applied to the spectrum of ULX-1.…”
Section: () ()supporting
confidence: 76%
“…A proper treatment of the observed properties of a slim disk requires additional parameters such as the viewing angle and the BH spin (Vierdayanti et al 2008(Vierdayanti et al , 2013Saḑowski 2009). However, Equations (4) and (5) are already good enough as a first-order approximation to test the consistency of a slim disk model for ULX-1.…”
Section: () ()mentioning
confidence: 99%
See 1 more Smart Citation
“…Also, if we consider the normalization parameter of the DISKPBB model in XM3 data, we may calculate another mass value for the compact object. We derived a true inner disk radius of R in √ cos i ≈ 40 km using the correction factor ξ = 0.353 and a spectral hardening factor κ = 3 (Vierdayanti et al 2008). Assuming a moderate disk inclination i = 60 and taking the mass correction factor as minimum (∼ 1.2) the mass of the compact object in X-6 can be calculated as M ∼ 10M for a non-spining BH.…”
Section: As Seen Inmentioning
confidence: 99%
“…Although no conclusive detections have been made to date, intermediate mass black holes are very intriguing astrophysical objects, with growing observational and theoretical evidence for their existence [1,2]. Their discovery would be a major breakthrough in our understanding of massive black hole formation [3,4], stellar-cluster evolution [5][6][7][8][9][10], and hyper/ultraluminous x-ray sources [11][12][13][14][15][16][17]. Coalescing intermediate mass black hole binaries (IMBHBs) are also the strongest candidate gravitational-wave (GW) sources accessible to ground-based interferometric detectors such as LIGO and Virgo [18,19].…”
Section: Introductionmentioning
confidence: 99%